English Language Teachers’ Expectations, Satisfaction, Needs and Performance in the Senior High Schools in Pangasinan, Philippines - Elsa Q Terre, Ed. D., Ph. D. (ASEAN Journal of Basic and Higher Education, 2020)
This study aimed to determine the English language teachers’ expectations, satisfaction, needs and performance in the Senior High Schools in Pangasinan and to develop an innovative language development plan. Descriptive correlational-comparative design was utilized in the study. Results showed that the level of expectations, satisfactions and needs of the Senior High School English language teachers in Pangasinan were unanimously high that needs to be addressed in order for them to work effectively in their respective schools. There is significant difference between and among expectations, satisfaction and needs of the English language teachers in the Senior High Schools along the seven areas or domains. The teaching performance of the Senior High School English language teachers in Pangasinan was very satisfactory. Thus, the level of expectations, satisfaction and needs of the Senior High School English language teachers didn’t affect their teaching performance. Furthermore, the researcher recommended that the DepEd officials concerned would try out the proposed innovative development plan concerning the needed activities and projects for the Senior High School teachers, likewise, the principals and assistant principals would help and guide new teachers to reduce the stress level that is associated with the multiple tasks of teaching and they should design staff development programs for them.